2006
DOI: 10.1207/s15516709cog0000_62
|View full text |Cite
|
Sign up to set email alerts
|

With the Future Behind Them: Convergent Evidence From Aymara Language and Gesture in the Crosslinguistic Comparison of Spatial Construals of Time

Abstract: Cognitive research on metaphoric concepts of time has focused on differences between moving Ego and moving time models, but even more basic is the contrast between Ego-and temporal-reference-point models. Dynamic models appear to be quasi-universal cross-culturally, as does the generalization that in Ego-reference-point models, FUTURE IS IN FRONT OF EGO and PAST IS IN BACK OF EGO. The Aymara language instead has a major static model of time wherein FUTURE IS BEHIND EGO and PAST IS IN FRONT OF EGO; linguistic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
438
1
35

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 789 publications
(478 citation statements)
references
References 62 publications
4
438
1
35
Order By: Relevance
“…Again, order judgments between two events were faster when the left hand was used to respond "before" and the right hand to respond "after" than with the opposite mapping. These data are consistent with the observation that people gesture from left to right when describing events that unfold in time (Núñez & Sweetser, 2006), and also with data from an off-line task asking participants to place stickers on a paper to represent events such as breakfast, lunch and dinner (Tversky, Kugelmass, & Winter, 1991). The latter study also found evidence suggesting that this horizontal mapping of time might be related to the habitual direction of reading and writing.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Again, order judgments between two events were faster when the left hand was used to respond "before" and the right hand to respond "after" than with the opposite mapping. These data are consistent with the observation that people gesture from left to right when describing events that unfold in time (Núñez & Sweetser, 2006), and also with data from an off-line task asking participants to place stickers on a paper to represent events such as breakfast, lunch and dinner (Tversky, Kugelmass, & Winter, 1991). The latter study also found evidence suggesting that this horizontal mapping of time might be related to the habitual direction of reading and writing.…”
supporting
confidence: 87%
“…In principle, the effect produced by the temporal words could result from a direct binding between the concepts of past and future to left and right responses (Pollmann & Maertens, 2005). Núñez & Sweetser (2006) showed that when we speak about the past we gesture to the left, whereas gestures referring to the future are directed towards the right. Consistently, the results of Experiment 2 showed that past/future meanings primed a motor response toward their congruent side.…”
Section: Discussionmentioning
confidence: 99%
“…behind a 'moving ego' on a path), Unknown is in front of ego (i.e. in front of a 'moving ego' on a path) (Núñez and Sweetser, 2006). In other words, time can be conceptualized in two different perspectives, namely moving-ego (ME) perspective, where time is considered to be a stationary entity, or moving-time (MT) perspective, where time is seen as a dynamic entity (Clark, 1973).…”
Section: 1: Backgroundmentioning
confidence: 99%
“…The Aymara-Indians, living secluded in the Andes, have been researched partly due to their perception of time and its linguistic expressions. In their language, they describe the past being in front of them using the word (nayra, "eye/front/sight") and the future is referred to with the word for back (qhipa, "back/behind") (Núñez & Sweetser, 2006). This understanding of temporality reminded me of post-structuralist perceptions of time and becoming as it very distinctly resonated with how time is conceptualized as interrelating syntheses in Deleuze's work (Deleuze, 1994;Williams, 2011).…”
Section: Introductionmentioning
confidence: 99%